Riley Child-Rhymes with Hoosier Pictures : Indiana Bicentennial Edition - Riley, James Whitcomb, 1849-1916 (Book collections on Project MUSE., 2016)
A must-have for Riley enthusiasts everywhere, this classic book has been faithfully reproduced for Indiana's state bicentennial. Now with an introduction by lifelong Riley enthusiast and former Indiana Poet Laureate Norbert Krapf, this charming book contains 39 of James Whitcomb Riley's signature poems, including "Old Aunt Mary's," "Little Orphant Annie," and "The Raggedy Man." Graced by noted Brown County artist Will Vawter's illustrations of such poems as "The Nine Goblins," "The Circus Day Parade," and "Barefoot, Hungry, Lean Ornery Boys," this book offers a look at how childhood was lived a century ago. First produced in 1890, Riley Child-Rhymes with Hoosier Pictures recalls simpler times gone by.